Dermatite factícia desencadeada pela síndrome de Münchausen Factitial dermatitis as a consequence of Munchausen syndrome - Náiade Maria Rêgo e Silva; Giannina Wanderley Petrucci; Esther Bastos Palitot; Mohamed Arbaqui Azzouz; Samir de Figueiredo Azzouz (Sociedade Brasileira de Dermatologia, 2010)
Dermatite factícia refere-se à condição em que as lesões cutâneas são autoinduzidas e resultam de algum distúrbio psiquiátrico. As lesões podem se apresentar de diversas formas e ser produzidas por grande variedade de meios. Apresenta-se um caso raro de paciente com dermatite factícia desencadeada pela síndrome de Münchausen, que se refere a indivíduos que intencionalmente produzem sintomas físicos com o intuito de atender a uma necessidade de receber atendimento médico frequente. Factitial dermatitis is a condition in which skin lesions are self-inflicted as the result of a psychiatric disorder. The lesions may be presented in various forms and produced by a wide variety of means. This report refers to the case of a patient with factitial dermatitis triggered by Munchausen syndrome, which refers to individuals who intentionally provoke physical symptoms in themselves in order to satisfy a need to receive frequent medical attention.